2020
DOI: 10.1002/hep4.1558
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Peroxisome Proliferator‐Activated Receptor Gamma Modulator CHS‐131 Improves Liver Histopathology and Metabolism in a Mouse Model of Obesity and Nonalcoholic Steatohepatitis

Abstract: CHS‐131 is a selective peroxisome proliferator‐activated receptor gamma modulator with antidiabetic effects and less fluid retention and weight gain compared to thiazolidinediones in phase II clinical trials. We investigated the effects of CHS‐131 on metabolic parameters and liver histopathology in a diet‐induced obese (DIO) and biopsy‐confirmed mouse model of nonalcoholic steatohepatitis (NASH). Male C57BL/6JRj mice were fed the amylin liver NASH diet (40% fat with trans‐fat, 20% fructose, and 2% cholesterol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Nevertheless, the reported effects of both studies argue for mild effects of empagliflozin in non-diabetic conditions, which thus necessitates a longer duration of treatment in order to achieve relevant hepatic benefits. In agreement with the above, when comparing the effects of empagliflozin with the effects of medications of other classes (i.e., liraglutide (glucagon-like peptide 1 receptor analogue), elafibranor (peroxisome proliferator-activated receptor alpha/delta agonist) or CHS-131 (selective peroxisome proliferator-activated receptor gamma modulator)) in the same mouse model experimental setting and for the same duration of treatment [19,20], the improvement in NAS score was more modest with empagliflozin, which suggested again weaker hepatic actions at normal/slightly elevated glucose levels compared with the other medications.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Nevertheless, the reported effects of both studies argue for mild effects of empagliflozin in non-diabetic conditions, which thus necessitates a longer duration of treatment in order to achieve relevant hepatic benefits. In agreement with the above, when comparing the effects of empagliflozin with the effects of medications of other classes (i.e., liraglutide (glucagon-like peptide 1 receptor analogue), elafibranor (peroxisome proliferator-activated receptor alpha/delta agonist) or CHS-131 (selective peroxisome proliferator-activated receptor gamma modulator)) in the same mouse model experimental setting and for the same duration of treatment [19,20], the improvement in NAS score was more modest with empagliflozin, which suggested again weaker hepatic actions at normal/slightly elevated glucose levels compared with the other medications.…”
Section: Discussionsupporting
confidence: 70%
“…The study design and methodology have been previously described [19,20]. Briefly, male C57BL/6JRj mice were fed an AMLN diet (D09100301, Research Diets Inc., New Brunswick, NJ, USA) that consisted of 40% fat, 2% cholesterol and 22% fructose for 36 weeks before the study initiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated earlier, new generations of ligands, referred to as noncanonical agonist ligands (NALs) and selective PPARy modulators (SPPARMs), hold promise in that respect. In fact, very recently, it has been shown how selective modulators of PPARy can improve liver histology without affecting body weight in biopsy-confirmed mouse model of nonalcoholic steatohepatitis (NASH) (148).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In brief, they showed that when Hrd1 (a subunit of the endoplasmic reticulum-associated degradation), is activated in hepatocytes, Acly (a major enzyme regulating lipogenesis) is degraded via ubiquitin modification, leading to hepatic steatosis amelioration and insulin sensitivity enhancement [37]. A great promise is also offered by selective PPAR-γ modulators, such as CHS-131 [62] that will need to be further assessed, as well as by medications that act early in the spectrum of the pathophysiology, such as glucagon-like peptide (GLP)-1 agonists, that can decrease liver fat, thus altering the natural history of the disease [26,[63][64][65]. It follows that relevant clinical trials are expected with great anticipation.…”
mentioning
confidence: 99%